An improved in silico algorithm for output visualization of DNA computing based on real-time PCR - Mohamed Saaid, Muhammad Faiz (Institute of Electrical and Electronics Engineers, 2008)
In the previous paper, a readout approach for the Hamiltonian Path Problem (HPP) in DNA computing based on the real-time polymerase chain reaction (PCR) was proposed. Based on this approach, real-time amplification was performed with the TaqMan probes and the TaqMan detection mechanism was exploited for the design and development of the proposed readout approach. The readout approach consists of two steps: real-time amplification in vitro using TaqMan-based real-time PCR, followed by information processing in silico to assess the results of real-time amplification, which in turn, enables extraction of the Hamiltonian path. The in silico information processing consists an algorithm to extract the Hamiltonian path based on result of in vitro real-time PCR experiment. However, this algorithm indirectly shows the Hamitonian path by only showing the location of each node for the HPP. Thus, in this paper, we modified the previous in silico algorithm such that the Hamiltonian path can be viewed directly after the in silico information processing of the TaqMan reactions based on real-time PCR is implemented. The modified algorithm can be easily implemented in the computerized application.